INTEGRASI KOSAKATA LOKAL TERNATE DALAM PEMBELAJARAN TEKS PROSEDUR MATA PELAJARAN BAHASA INDONESIA SISWA SMA - Nurbaya, Nurbaya (Jurnal Pendidikan dan Ekonomi (JUPEK), 2025)
Learning Indonesian requires students to understand various types of texts, one of which is procedural texts, which explain the steps for carrying out an activity. However, procedural text learning in schools is often poorly connected to the local cultural context, thus not providing a relevant learning experience for students. This study aims to describe the integration of local Ternate vocabulary into procedural text learning for high school students and analyze its impact on text comprehension and cultural appreciation. The method used is descriptive qualitative research through classroom observations, student assignment analysis, and teacher interviews. The results show that the integration of local vocabulary, especially those related to culinary arts, traditional tools, and cultural activities, increases student engagement, enriches vocabulary, and strengthens understanding of procedural text structures. In addition, contextual learning based on local culture contributes to the preservation of regional languages ​​and the cultural identity of Ternate students. This study emphasizes the urgency of an ethnopedagogical approach in Indonesian language learning.